1880-81 Ga. Laws 154 - (:unkn) unknown (My University, 1880)
An Act to make Penal the Intentional Pointing, or Aiming of Fire-arms at Another, whether Loaded or Unloaded, § 1: Prohibited pointing a gun or pistol, loaded or unloaded, at another. Violators guilty of a misdemeanor.
Keywords: BRANDISHING